Health-related quality of life in patients with a germline BRCA mutation and metastatic pancreatic cancer receiving maintenance olaparib. (28th September 2019) - Hammel, P; Kindler, H L; Reni, M; Van Cutsem, E; Macarulla, T; Hall, M J; Park, J O; Hochhauser, D; Arnold, D; Oh, D -Y; Reinacher-Schick, A; Tortora, G; et al.
Abstract: Background: Patients with metastatic pancreatic cancer often have a detriment in health-related quality of life (HRQoL). In the randomized, double-blind, phase III POLO trial progression-free survival was significantly longer with maintenance olaparib, a poly(ADP-ribose) polymerase inhibitor, than placebo in patients with a germline BRCA1 and/or BRCA2 mutation (gBRCAm) and metastatic pancreatic cancer whose disease had not progressed during first-line platinum-based chemotherapy. The prespecified HRQoL evaluation is reported here. Patients and methods: Patients were randomized to receive maintenance olaparib (300 mg b.i.d.; tablets) or placebo. HRQoL was assessed using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30-item module at baseline, every 4 weeks until disease progression, at discontinuation, and 30 days after last dose. Scores ranged from 0 to 100; a ≥10-point change or difference between arms was considered clinically meaningful. Adjusted mean change from baseline was analysed using a mixed model for repeated measures. Time to sustained clinically meaningful deterioration (TSCMD) was analysed using a log-rank test. Results: Of 154 randomized patients, 89 of 92 olaparib-arm and 58 of 62 placebo-arm patients were included in HRQoL analyses. The adjusted mean change in Global Health Status (GHS) score from baseline was <10 points in both arms and there was no significant between-group difference [−2.47; 95% confidence interval (CI) −7.27, 2.33; P = 0.31]. Analysis of physical functioning scores showed a significant between-group difference (−4.45 points; 95% CI −8.75, −0.16; P = 0.04). There was no difference in TSCMD for olaparib versus placebo for GHS [ P = 0.25; hazard ratio (HR) 0.72; 95% CI 0.41, 1.27] or physical functioning ( P = 0.32; HR 1.38; 95% CI 0.73, 2.63). Conclusions: HRQoL was preserved with maintenance olaparib treatment with no clinically meaningful difference compared with placebo. These results support the observed efficacy benefit of maintenance olaparib in patients with a gBRCAm and metastatic pancreatic cancer. ClincalTrials.gov number: NCT02184195.